Guidelines of the Brazilian Society of Oncologic Surgery for pelvic exenteration in the treatment of cervical cancer. Issue 5 (27th November 2019) - Laporte, Gustavo A.; Zanini, Lucas A. G.; Zanvettor, Paulo H.; Oliveira, Alexandre F.; Bernado, Enio; Lissa, Fernando; Coelho, Manoel J. P.; Ribeiro, Reitan; Araujo, Raphael L. C.; Barrozo, Abner J. J.; da Costa, Alexandre F.; de Barros Júnior, Amario P.; et al.
Abstract: Background and Objectives: The primary treatment for locally advanced cases of cervical cancer is chemoradiation followed by high‐dose brachytherapy. When this treatment fails, pelvic exenteration (PE) is an option in some cases. This study aimed to develop recommendations for the best management of patients with cervical cancer undergoing salvage PE. Methods: A questionnaire was administered to all members of the Brazilian Society of Surgical Oncology. Of them, 68 surgeons participated in the study and were divided into 10 working groups. A literature review of studies retrieved from the National Library of Medicine database was carried out on topics chosen by the participants. These topics were indications for curative and palliative PE, preoperative and intraoperative evaluation of tumor resectability, access routes and surgical techniques, PE classification, urinary, vaginal, intestinal, and pelvic floor reconstructions, and postoperative follow‐up. To define the level of evidence and strength of each recommendation, an adapted version of the Infectious Diseases Society of America Health Service rating system was used. Results: Most conducts and management strategies reviewed were strongly recommended by the participants. Conclusions: Guidelines outlining strategies for PE in the treatment of persistent or relapsed cervical cancer were developed and are based on the best evidence available in the literature.